Hardy and the Heroine: A Study of the Development of the Heroine in Hardy's Fiction - Shaw, Maureen (My University, 1973)
This thesis traces Thomas Hardy's portrayal of the heroines in his novels and indicates how she is used to provide a focus for the problems and issues he presents. The thesis begins by suggesting that a standard portrayal of the heroine had emerged in Victorian fiction by about 1850 that was considerably modified by female writers such as Charlotte and Emily Brontë, Mrs. Gaskell and George Eliot, and finally, by Hardy himself. The study of some of Hardy's earlier novels reveals that he also created a stereotype of his own. However, the examination of a selection of his later novels makes it clear that he gradually enlarged his scope in order to present a full, detailed and original sense of woman's personal and social predicament.
Keywords: English; English Language and Literature; English Language and Literature